1982
DOI: 10.1111/j.1475-097x.1982.tb00035.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of physical training in elderly subjects with special reference to energy‐rich phosphagens and myoglobin in leg skeletal muscle

Abstract: Energy-rich phosphagens and myoglobin were determined in leg skeletal muscles of seven, 61- to 80-year-old, apparently healthy male subjects. The study repeated after the participants had been exercising on an ergometer bicycle twice weekly for 6 weeks. Before training, myoglobin and all intramuscular energy-rich phosphagens were within the range recorded for a larger series of subjects of similar age. When re-examined after training the myoglobin level remained the same but creatine decreased significantly an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…According to human cross-sectional studies, however, [Mb] in trained subjects was not observed to be higher than that in sedentary subjects (Jansson and Sylve n 1981;Jansson et al 1982Jansson et al , 1983Sylve n et al 1984). In addition, the results from human training experiments vary from author to author (MoÈ ller and Brandt 1982;Svedenhag et al 1983;Terrados et al 1986Terrados et al , 1990, and similarly with et al 1998). MoÈ ller and Brandt (1982) submitted elderly subjects to endurance training and observed no resultant change in [Mb].…”
Section: Introductionmentioning
confidence: 49%
“…According to human cross-sectional studies, however, [Mb] in trained subjects was not observed to be higher than that in sedentary subjects (Jansson and Sylve n 1981;Jansson et al 1982Jansson et al , 1983Sylve n et al 1984). In addition, the results from human training experiments vary from author to author (MoÈ ller and Brandt 1982;Svedenhag et al 1983;Terrados et al 1986Terrados et al , 1990, and similarly with et al 1998). MoÈ ller and Brandt (1982) submitted elderly subjects to endurance training and observed no resultant change in [Mb].…”
Section: Introductionmentioning
confidence: 49%
“…In support, McCully and others [108] reported a small but significant age-related decrease in the ratio of PCr to inorganic phosphate using magnetic resonance spectroscopy. Interestingly, Moller and Brandt [112] exercised seven 61-to 80-year-old, apparently healthy male subjects on a cycle ergometer twice weekly for 6 weeks. Following the training period, the ratio between PCr and total creatine increased, and a small but significant rise was observed for the ATP/adenosine diphosphate (ADP) ratio.…”
Section: Substrate Availabilitymentioning
confidence: 99%
“…In our recent study of the [Mb] during compensatory hypertrophy in rats (Masuda et al 1997), we have observed that the [Mb] of the plantaris muscle was maintained at the control level during the compensatory hypertrophy. These results, however, cannot be directly applied to human muscle since a discrepancy has been observed between the Mb adaptations to exercise training in humans (Jansson and Sylve n 1981;Jansson et al 1982Jansson et al , 1983MoÈ ller and Brandt 1982;Svedenhag et al 1983;Sylve n et al (1984) and in animals (Hickson 1981;Hickson and Rosenkoetter 1981;Harms and Hickson 1983;Beyer and Fattore 1984;Hickson et al 1984); the [Mb] of animal skeletal muscle was increased by endurance training but that in humans was not. Therefore, the eects of RT on the [Mb] in humans have not yet been described.…”
Section: Discussionmentioning
confidence: 53%
“…Myoglobin (Mb) has been thought to relate to oxidative metabolism and to have several roles ± facilitated diusion, oxygen storing and mediation of oxidative phosphorylation (Wittenberg 1970;Kagen 1973;Cole 1982;Gayeski et al 1985;Wittenberg and Wittenberg 1989), and the Mb concentration ([Mb]) has been found to be associated with mitochondrial enzyme activity (Wittenberg 1970) and with the capillary supply (Reis and Wooten 1970). The adaptation of Mb in response to exercise has been studied solely in conditions of endurance training in animals (Hickson 1981;Hickson and Rosenkoetter 1981;Harms and Hickson 1983;Beyer and Fattore 1984;Hickson et al 1984) and humans (Jansson and Sylve n 1981;Jansson et al 1982Jansson et al , 1983MoÈ ller and Brandt 1982;Svedenhag et al 1983;Sylve n et al 1984). The [Mb] in rat skeletal muscles has been shown to be increased by endurance training, although that in human skeletal muscle was not.…”
Section: Introductionmentioning
confidence: 97%